Work in the Lives of Finnish Women as Reflected in Contemporary Finnish Social Research and Women’s Literature - Kasierska-Szura, Katarzyna (Folia Scandinavica Posnaniensia, 2007)
Work related values are to be found among the most cherished by Finns in any Finnish value survey ever conducted. Women constitute 49% of the whole of Finnish labour force. In contemporary Finnish novels however, pictures of females at work are much less frequent than those of working males. The author of this article discusses the actual meaning of work in the Finnish society and claims that the significance of work for both sexes is equally evident - only in the case of women it is manifested differently. Finnish women - as well as female characters in contemporary Finnish novels by women authors - express themselves acting rather than pondering just like their male counterparts.